1985
DOI: 10.1021/jo00221a003
|View full text |Cite
|
Sign up to set email alerts
|

Structural and stereochemical studies of naturally occurring longipinene derivatives

Abstract: dissolved in dioxane (40 mL) was hydrogenated over palladiumon-barium sulfate catalyst (0.02 g) in the presence of quinoline (0.2 g). When the hydrogen absorption ceased, the catalyst was filtered off and the solvent was removed in vacuo, leaving a residue (0.081 g), which was dehydrated in xylene-tetrahydrofuran (4:1 v/v) solution with boron trifluoride etherate (0.9 mL) in the presence of hydroquinone (0.02 g) by boiling in a reflux condenser during 3.5 h. After cooling, the reaction mixture was treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
50
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 2 publications
1
50
0
Order By: Relevance
“…Compound 4 (5.25% overall yield from the extract) was obtained from fractions 84-100. The physical and spectral data were identical to those reported [15]. (4R,5S,7S,8S,9S,10R,11R) Molecular modelling: Molecular mechanics were carried out with the Merck molecular force field calculations (MMFF94), as implemented in the Spartan'04 program (Wavefunction, Inc., Irvine, California).…”
mentioning
confidence: 84%
“…Compound 4 (5.25% overall yield from the extract) was obtained from fractions 84-100. The physical and spectral data were identical to those reported [15]. (4R,5S,7S,8S,9S,10R,11R) Molecular modelling: Molecular mechanics were carried out with the Merck molecular force field calculations (MMFF94), as implemented in the Spartan'04 program (Wavefunction, Inc., Irvine, California).…”
mentioning
confidence: 84%
“…Bioactive principles require an accurate description of their three-dimensional structures to allow molecular visualization and to understand possible interactions with target biomole- cules. In previous works, longipinane derivatives 1-3 were used as relevant key compounds to elucidate the stereochemistry, conformation, and absolute configuration of these types of substances [8,9]. Thus, when the ECD of 1 and its diacetate derivative 2 were compared with that of closely related (+)-vulgarone, a good correspondence among them was found.…”
Section: Introductionmentioning
confidence: 99%
“…1), are generally found as complex mixtures of esters [6]. The relative stereochemistry of the C7, C8, and C9 acyloxy groups at the seven-membered ring was established by singlecrystal X-ray diffraction of rastevione acetate (10) [7] and by chemical transformation of rastevione (9) in compounds of type 1 and 3 [8]. The absolute configuration of this group of substances was found to be the same as (+)-longipinene and was established by comparing the electronic circular dichroism (ECD) curves of 1 and its diacetate 2 with vulgarone B [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical studies on the large genus Steuia revealed that several functionalized longipinenes (Amaro et al, 1988;Gil et al, 1987;Joseph-Nathan et al, 1989;Roman et al, 1985) bearing keto, ester, and/or hydroxyl groups are representative substances of this taxon (Zdero et al, 1988). One of the most important groups of these compounds comprises the diesters of longipin-2-ene-7/3,9a-diol-l-one (1) (Table 1) in which the most common ester residues are angelates (Z-2-methyl-2butenoates), tiglates (E-2-methyl-2-butenoates), seneciates (3-methyl-2-butenoates), methacrylates (2methylpropenoates) and acetates (Joseph-Nathan et al, 1989).…”
Section: Introductionmentioning
confidence: 99%